PERAN LEMBAGA PENYIARAN PUBLIK RADIO REPUBLIK INDONESIA ATAMBUA DALAM PELAKSANAAN PEMBANGUNAN DI WILAYAH PERBATASAN NKRI-RDTL - Fransiskus Atok; Herminus Kefi; Bernardo Idalina Leto (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2026)
This study focuses on the role of the Public Broadcasting Institution Radio Republik Indonesia as a communication media in implementing development on the border of NKRI-RDTL. The purpose of this study is to describe, analyze, and interpret the role of Radio Republik Indonesia as a media for disseminating information on the implementation of the cross-border festival and the fulan fehan festival which have become annual agendas of the Belu district government. The type of research used in dissecting this problem is descriptive research, namely a type of research that describes a phenomenon or event as it is and analyzes data using a qualitative approach. In digging up information from informants, the author uses interview guidelines as a tool in conducting interviews. The interview begins with the Head of RRI Atambua, and the information moves to the Head of Broadcast, Program Director, Broadcast Director and Studio Technician. The results of the study show that LPP-RRI Atambua Station has carried out its function as an information.